Penilaian Kinerja Karyawan Menggunakan Kombinasi Metode Multi-Objective Optimization by Ratio Analysis (MOORA) dan Pembobotan Entropy - Ade Surahman (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
Performance appraisal is a process for identifying employee strengths and areas of development, providing a basis for decision-making regarding promotion, skills development, and recognition of good performance. The combination of MOORA method and entropy weighting is a comprehensive approach in multi-criteria decision making. MOORA provides a framework for assessing and filtering alternatives based on the ratio of comparison to positive and negative ideal solutions, while entropy weighting contributes by taking into account the degree of uncertainty or chaos on each criterion. The ranking results provide recommendations for rank 1 on behalf of Employee A with a final value of 0.4522, rank 2 on behalf of Employee B with a final value of 0.4428, and rank 3 on behalf of Employee D with a final value of 0.4156.